Pathology of Ascites Syndrome in Broiler Chicken - Jacob Alexander (Department of Pathology, College of Veterinary and Animal Sciences, 1996)
The post mortem reports maintained at the Department of Pathology during the period 1985 – 95 revealed that the prevalence of ascites syndrome (AS) was gradually on the increase. Investigations carried out on field cases showed that AS occurred in better managed farms and also in farms where the feed did not contain aflatoxin. The bacteriological study and screening of ascetic fluid in electron microscope for virus did not indicate a microbial etiology. Two separate experiments were conducted with vencob strain of broiler chicken. In each of the experiments the feed additives were mixed in the feed and fed ad libitum from the second week onwards. The body weight was recorded weekly. The PCV, haemoglobin, serum protein, albumin, globulin, albumin – globulin ratio, sodium and potassium were estimated at fortnightly intervals. At the eighth week the live birds were slaughtered and the gross and histopathological lesions were evaluated. The organ weight, relative organ weight and RV : TV were also evaluated. In the first experiment 50 chicks of two weeks of age were randomly divided into three treatment groups of 12 each. The control group consisted remaining 14 chicks. The treatment groups were given monensin sodium, pure sodium chloride (99.99%) and furazolidone in the feed at the rate of 360, 25, 000 and 800 ppm respectively. The birds in the monensin group were stunted due to less feed and water intake. The serum biochemistry, lesions, organ weight and a lesser RV : TV indicated that monensin might not cause AS. The sodium chloride group initially exhibited excessive thirst, diarrhoea, hyperaemic skin and distended abdomen but by the end of the eighth week none had ascites on post mortem examination. The PCV, haemoglobin, serum Na++ and RV : TV were higher than the control. The furazolidone group exhibited nervous symptoms and one bird died of ascites syndrome at the 45th day of treatment. The body weight, PCV, haemoglobin, serum protein, albumin, globulin, potassium and organ weight were lesser than the control group. Congestion, hydropericardium and nephrosis were noticed in the birds. Ectopic cartilaginous nodules, pulmonary congestion and oedema, loss of striation and separation of myocardial fibers and severe diffuse granular degeneration of hepatocytes were also noticed. The second experiment consisted of 80 chicks of two weeks age randomly divided into 8 groups of 10 each. Furazolidone was administered at a higher dose (1000 ppm) and common salt was given instead of sodium chloride at the same dose rate (25,000 ppm). Cephalexin was also administered to another group at the rate of 800 ppm. Two salts of cobalt namely chloride and nitrite were given to two separate groups at 600 ppm each to elucidate its aetiological role. In addition, two groups were utilized for transmission studies using the ascetic fluid and liver suspension collected aseptically from field cases. The birds in the furazolidone group showed nervous symptoms, and was stunted. One bird died of ascites on the 53rd day of the treatment. The PCV, haemoglobin, serum protein, albumin, globulin, Na++ , K+ and organ weight were lesser while the relative organ weight and RV : TV were higher than the control group. These observations suggested that furazolidone was a potential agent which could cause AS. In the common salt group three birds died of AS on the 5th, 11th and 24th days of treatment. They showed sequential progressive lesions. Increased feed and water intake, respiratory distress, and distended abdomen were noticed. Their body weight, PCV, haemoglobin, serum Na++ and K+ content were higher than the control. Congestion, oedema, haemorrhage and ectopic cartilaginous nodules were noticed in the lungs. Severe congestion of the central and portal veins and thickening of the Glisson’s capsule were seen in the liver. Mesangial cell proliferation, and thickening of the basement membrane of the glomerular tuft were evident. The weight and relative weight of the heart, RV and LV were the highest among all the groups. The RV : LV was higher when compared to the control. The weight of the spleen, lungs, liver and intestine was greater than the control. These results indicated that common salt was more potent than sodium chloride in precipitating AS. In the cobalt chloride and nitrite groups, the birds showed a reddened skin and had a lesser body weight than the control. The PCV, haemoglobin and serum Na++ were higher while the serum K+ and absolute organ weight were lesser than the control. The RV : TV ratio was higher than the control in both the groups. These suggested that excess amounts of cobalt in chicken feed might cause ascites. When cephalexin was given to the birds no noticeable symptoms were observed. The serum Na++ , K+ , organ weight, relative organ weight and RV : TV were lesser than the control and it did not cause AS. Transmission studies using liver suspension and ascetic fluid injection intraperitoneally did not cause ascites. A microbial etiology therefore couldnot be elucidated.